Application of Action Research Methodology in Improving the Processing Quality of Local Rice in the Dadin-Kowa Community of Gombe State Nigeria - Festus Annor-Frenpong; Benjamin Adamu Shamaki; Livingstone Kobina Sam-Amoah; Albert Obeng Menaah (Journal of Agricultural Extension, 2010)
Dadin Kowa community of Gombe State is noted for rice production due to the presence of dams that ensure all year rice production. However, low patronage and high price of local rice in local markets are putting many farmers and women processors out of business. The paper shares results of an action research process that led to the determination of rice consumer preferences and strengthening of women processors group to improve processing quality of local rice. Forty-seven respondents were sampled using purposive and snow balling sampling techniques to provide views on consumers’ preference for rice. Frequencies and percentages were used to analyse and describe the results of the study. The study concluded that paddy rice contains 0.21% stones and sand which could be eliminated using a destoner. Furthermore, a locally manufactured wooden winnower reduces winnowing time by 25 minutes and improves purity by 20% when compared to traditional winnowing process. The processed rice from the action methodology process received 30 and 16 point difference for appearance and acceptability by consumers respectively when compared to the traditional method. Finally, an extra income of N2400 was realised per 100kg bag of improved rice. Both the study methodology and conclusions have implications for agricultural training and extension delivery, which together help forge functional linkages among the major sub-systems of the agricultural knowledge systems. Resultantly, clientele’s experience is integrated into total learning process, thereby entraining the planned change.